Young, old, massive: Steps to understanding globular cluster formation. Issue Volume 14:Issue S351(2019) (May 2019) - Harris, William E.
Abstract: On observational grounds we now know a huge amount about the characteristics of massive star clusters in galaxies of all types, from the smallest dwarfs to the most massive giants and even into the Intracluster Medium. The old globular clusters (GCs) in particular exhibit a high degree of uniformity across all these environments in their physical properties including scale size, luminosity distribution, metallicity distribution, and age. As survivors of a long period of dynamical evolution, they are "unusual, but not special" among star clusters. The past few years have seen major advances in theoretical modelling that are starting to reveal how these massive star clusters formed in the early stages of galaxy evolution. Several suites of models point to their emergence in GMCs (Giant Molecular Clouds), which provide the turbulent big reservoirs of gas within which star clusters can be built. At cluster masses ∼10 5 M ⊙ and above, clusters form hierarchically through a nearly equal combination of direct gas accretion, and mergers with smaller clusters scattered throughout the GMC. GCs and YMCs (young massive clusters) in this high mass range should therefore be composite systems right from birth. To make such high-mass clusters, host GMCs of ∼10 7 M ⊙ are needed, and these are most commonly found in galaxies at redshifts z ≳ 2.